A New Method of Edge Crack Suppression in the Rolling Process of Magnesium Alloy Sheet and Study on the Method of Cathodic Protection - Xintao Li; Yanchun Zhu; Haibin Li; Yong Niu; Chenglong Yang (Advances in Materials Science and Engineering)
A new method is proposed to solve edge cracking and corrosion in rolling process of the magnesium alloy plate. Usually in the process, the edge cracking is caused by the great temperature difference between the edge and the center of the alloy plate and the corrosion is by water in air. The method uses hot air wrapped around the plate to perfectly prevent edge cracking and corrosion. The method also includes cathodic protection for the magnesium alloy based on electrochemistry. The suppression of cathodic protection on the chemical activity of the magnesium alloy was studied. The experiment shows that the new method of edge heating with hot air wrapping is effective to prevent edge cracking and corrosion. Also, the cathodic protection can effectively suppress the chemical activity of the magnesium alloy and improve the surface quality in the rolling process of the magnesium plate, which provides a new concept in rolling process of the magnesium alloy.